The role of committee attitude on company's decision for sponsoring sports events - Billy Castyana; Zainudin Amali; Mugiyo Hartono; Agus Pujianto; Tandiyo Rahayu; Mohammad Arif Ali; Gustiana Mega Anggita (Journal Sport Area, 2022)
Partnerships with companies or sponsorships cannot be separated in the implementation of sporting events; even sponsorship is a significant investment given by companies in the sports industry. However, every company has considerations before sponsoring a sporting event, one of the influencing factors is the attitude of the organizing committee to the company that is a potential sponsor. The purpose of this study is to demonstrate the importance of the committee's attitude toward the company's decision to sponsor a sporting event. By using quantitative descriptive research and survey methods, this study collected data from 33 companies that met the criteria of having sponsored a sporting event and were willing to participate in the study by completing a willingness sheet. The data is taken from a questionnaire filled out by the Company Owner or the company's Marketing Department by first answering questions about the duration of work in the company. Then, respondents responded to statements that came from four indicators, namely the relationship between the committee and the company, the company's interest in the committee, the committee provided a sense of comfort for the company in working together, and the company felt benefited from working together, with the answer strongly agree, agree, disagree, and strongly disagree. After that, the data was analyzed using excel and shown in graph on percentages to explain that the indicator of comfort in working together plays the highest role with a total of 42.42% strongly agree and 48.48% agree. Indirectly, this facet provides information to future sports organizers to assist them in obtaining funding for sports events through a win-win situation or mutualistic relationship.